Eleventh Volume: Composite Materials—Testing and Design 1993
DOI: 10.1520/stp12626s
|View full text |Cite
|
Sign up to set email alerts
|

High Strain Rate Effects for Composite Materials

Abstract: We have been developing the capability to characterize the high strain rate response of continuous fiber polymer composites. The data presented cover strain rates from 0/s to 3000/s. A combination of test machines and specimen geometries was investigated. Strain rates from 0 to 100/s were generated using conventional and high-speed hydraulic test machines. Strain rates from 10 to 1000/s were generated using a high-energy drop tower, and rates from 1000 to 3000/s were generated using a split Hopkinson bar. Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…The average compression strength increased by a significant 87% between quasi-static and 126 s À1 strain rates. The increase in compression modulus and strength may be attributed to the viscoelastic effects in the matrix materials and the time dependent nature of damage accumulation [29,34]. The Y-C strain rate equations fit the experimental results well for the dynamic compressive modulus and strength over the entire strain rate range in this study (see Fig.…”
Section: Compression Mechanical Propertiessupporting
confidence: 65%
See 2 more Smart Citations
“…The average compression strength increased by a significant 87% between quasi-static and 126 s À1 strain rates. The increase in compression modulus and strength may be attributed to the viscoelastic effects in the matrix materials and the time dependent nature of damage accumulation [29,34]. The Y-C strain rate equations fit the experimental results well for the dynamic compressive modulus and strength over the entire strain rate range in this study (see Fig.…”
Section: Compression Mechanical Propertiessupporting
confidence: 65%
“…The increase in tensile modulus and strength is generally explained by a combination of several factors including the viscoelastic nature of the polymeric matrix [29], i.e. stiffening with increased rate of loading, and following Welsh and Harding [30], the woven structure and geometry of the composite.…”
Section: Tensile Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Strain rates from 0 to 100 s Ϫ1 were generated using conventional and high-speed hydraulic test machines, those from 10 to 1000 s Ϫ1 were generated using a high energy drop tower, and those from 1000 to 3000 s Ϫ1 were generated using a split Hopkinson bar. The experimental results indicated an increase in both the compression and the tensile properties (strength and modulus) with increasing strain rate.…”
mentioning
confidence: 99%
“…It revealed that the most common dynamic compression test method utilized is the split Hopkinson bar technique (SPHB) [6][7][8][9][10], which generates strain rates of the order of 1000/s. The second most common test technique, instrumented drop weight system, has been used by Montiel and Williams [11], Groves et al [12], Hsiao et al [13,14] and Lifshitz [15] to investigate compressive properties of composite. The drop weight system has certain advantages but the system is very sensitive to contact conditions between the impactor and specimen, and to spurious noise from ringing and vibrations.…”
Section: Introductionmentioning
confidence: 99%